Prostitution Policies in Switzerland and the City of Zurich : A Critical Frame Analysis of Official Documents and NGO Papers - Isler, Corinne (Helsingfors universitet, 2016)
The phenomenon of prostitution has been controversial in many countries, including Switzerland. Policy regimes on prostitution differ drastically between countries. In recent years, there have been two opposing trends regarding the reform of prostitution laws. Some countries, such as Germany and the Netherlands, have moved towards legalisation and normalisation of the sex industry. Prostitution is thereby regarded as a normal trade and feminist supporters of this model focus mainly on legal rights and improved working conditions for people who sell sex. In contrast, other countries, including Sweden, Norway, Iceland and most recently France, have adopted a policy regime based on the assumption that prostitution per se is a form of violence against women and should thus be eradicated. In Switzerland, prostitution has been de facto legalised since 1942 and the cantons and municipalities can adopt their own policies regarding the regulation of the industry. The City of Zurich adopted a new Prostitution Industry Regulation in 2011, which brought a number of changes regarding licencing procedures and zoning laws for street prostitution and brothels. This research aims at examing the ways in which prostitution has been framed by different socio-political actors in Switzerland and the City of Zurich in particular. For this purpose I analyse a number of official documents published by the Swiss government and the City of Zurich as well as NGO papers regarding prostitution, all published between 2010 and 2015. The analysis draws on the methodological approach of critical frame analysis, which adopts a constructivist perspective on policy problems. It is assumed that different ways of constructing a problem also lead to different suggestions for solutions. For Switzerland and Zurich, two main frames could be identified and I outline their central features as well as their internal inconsistencies. Despite the differences between these two frames, they have some important aspects in common. Both frames take a clearly ...